Early predictors of career development: A 10-year follow-up study - Ferreira, Joaquim Armando (2007)
This paper presents empirical findings from a 10-year longitudinal study of the educational and occupational socialization of 445 participants who were about 7 years old when first tested, and about 17 years old at the fourth time of measurement. In addition to collecting psychological measurements from the participants, behavioral reports were collected from significant others, specifically parents and teachers. Findings demonstrated that the life/career evolution of the participants can be understood only when taking into account the dynamic interaction between the unique personal characteristics of individuality of each person and the psychosocial theatre within which the person's development takes place. Using the life-span, life-space framework of Super, and the Developmental-Contextual model from Vondracek, different emerging early predictors with unique impact on the process of educational and occupational socialization were identified, especially with respect to the probability of dropping out of school. Results in terms of gender, parental influences, psychological characteristics, and social context are discussed with regard to their potential implications for psychological interventions in schools, families, and occupational settings, as well as with regard to personal counseling in what concerns the management of life circumstances and behavioral ecosystems.